Estimation of discrimination threshold for emulsified chicken oil in chicken broth. (9th February 2022) - Watanabe, Genya; Ishida, Shota; Motoyama, Michiyo; Duconseille, Anne; Takita, Keigo; Nakajima, Ikuyo; Tajima, Atsushi; Sasaki, Keisuke
Abstract: Although fat content affects the texture and flavor of meat and meat products, the fat discrimination thresholds are unknown. This study aimed to elucidate the discrimination threshold of fat in meat products using broth from chicken thigh meat as a meat taste model. In Experiment 1, triangle tests were conducted between 1%, 0.2%, 0.04%, and 0.008% (w/v) chicken oil‐supplemented broth and broth without chicken oil. The results indicated the discrimination threshold to be between 0.04% and 0.008% (w/v). In Experiment 2, similar triangle tests were conducted using oil supplementation at 0.1%, 0.0333%, 0.0111%, and 0.0037% to refine the discrimination threshold. Logistic regression analysis revealed that the discrimination threshold of emulsified chicken oil in chicken broth was 0.0387% (w/v). We demonstrated that chicken oil made a sensory difference in chicken broth at a low concentration and indicates that the chicken oil strongly affects the sensory characteristics of chicken broth.